Byrsonima fagifolia Niedenzu Apolar Compounds with Antitubercular Activity - Higuchi, Célio Takashi [UNESP]; Sannomiya, M. [UNESP]; Pavan, Fernando Rogério [UNESP]; Leite, S. R. A. [UNESP]; Sato, D. N.; Franzblau, S. G.; Sacramento, Luis Vitor Silva do [UNESP]; Vilegas, Wagner [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (Hindawi Publishing Corporation, 2011)
Bioassay-guided fractionation of the chloroform extract of Byrsonima fagifolia leaves led to the isolation of active antitubercular compounds alkane dotriacontane (Minimal Inhibitory Concentration-MIC, 62.5 mu g mL(-1)), triterpenoids as bassic acid (MIC = 2.5 mu g mL(-1)), alpha-amyrin acetate (MIC = 62.5 mu g mL(-1)), a mixture of lupeol, alpha- and beta-amyrin (MIC = 31.5 mu g mL(-1)) and a mixture of lupeol, and acetates of alpha- and beta-amyrin (MIC = 31.5 mu g mL(-1)). The antimycobacterial activity was determined by the Microplate Alamar Blue Assay (MABA) and the structures of promising compounds were determined by spectroscopic analysis. This investigation constitutes the first report of a chemical and antitubercular study of apolar compounds from B. fagifolia Niedenzu (IK).